Drug-related problems and its predictors among hospitalized heart failure patients at Jimma Medical Center, South West Ethiopia: prospective interventional study - Birbirsa Sefera; Mestawet Getachew; Yadeta Babu; Firomsa Bekele; Korinan Fanta (BMC Cardiovascular Disorders, 2022)
Abstract Background Drug-related problems are associated with high mortality, complications, prolonged hospital stay, compromised quality of life, and increased healthcare costs. This problem is high in patients hospitalized with chronic conditions such as heart failure. However, there are limited studies conducted on this area, particularly in Ethiopia. Objective To evaluate drug-related problems, their predictors, and clinical pharmacist intervention among hospitalized heart failure patients at Jimma Medical Center, Ethiopia. Methods and participants A prospective interventional study was conducted among hospitalized heart failure patients from September 30, 2020, to May 28, 2021, at Jimma Medical Center. Drug-related problems were sorted based on the Pharmaceutical Care Network Europe drug classification tool version 9.0. Patient's specific data were collected using a structured questionnaire. Data was analyzed using statistical software package version 23.0. Multivariate logistic regression analysis was used to identify independent predictors of drug-related problems occurrence and statistical significance was considered at a p value < 0.05. Results A total of 237 heart failure patients were included in this study. The mean (SD) age was 49.06 + 17.79. About two-thirds (66.2%) of study patients had at least one drug-related problem during their hospital stay. A total of 283 drug-related problems were identified among 157 patients. Treatment effectiveness-related problem (55.48%) was the most common observed drug-related problem. The independent predictors of drug-related problems were khat chewing [AOR = 3.25, 95% CI = (1.46–7.23)], hospital stay > 18 days [AOR = 3.77, 95% CI = (1.93–7.37)]; presence of comorbid condition [AOR = 2.59, 95% CI = (1.35–4.96)] and polypharmacy [AOR = 2.94, 95% CI = (1.54–5.61)]. Conclusion The prevalence of drug-related problems was high among hospitalized heart failure patients in the study area. Chewing khat, prolonged hospital stay, comorbidity, and polypharmacy were the predictors of drug-related problems. Hence, to overcome these problems, clinical pharmacists, physicians, and other health professionals have to work in collaboration.